(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The abundance, foraging behavior, and diurnal and seasonal dynamics of the pollinator insects in chili ecosystem, and the impact of the pollinator insects on chili production was studied at the Bangabandhu Sheikh Mujibur Rahman Agricultural University, (BSMRAU) Gazipur, Bangladesh using the chili variety BARI Morich 2. The crop was cultivated in natural, supplemented insect and selfpollination conditions. The lime butterfly, honey bee, carpenter bee and sweat bee were found in the chili ecosystem. Honey bee depicted significantly the highest abundance and visitation frequency and carpenter bee was found as the most rapid forager. The diurnal and seasonal abundance of the pollinator insects was fluctuated and the peak abundance was found at 11.00 hour of the day. Abundance of lime butterfly, honey bee and carpenter bee revealed negative relationship with maximum and minimum temperatures, and positive relationship with relative humidity and rainfall. Abundance of sweat bee was positively correlated with maximum and minimum temperatures and rainfall, and negatively correlated with relative humidity. The chili plants exerted vulnerable response to insect pollination producing significantly the higher number of fruits per plant, fruit length, diameter and weight, number of seed per fruit, seed weight and yield. Bangladesh J. Agril. Res. 46(3): 297-306, September 2021